Phylogenomics of Fargesia and Yushania reveals a history of reticulate evolution. Issue 6 (8th April 2021) - Ye, Xia‐Ying; Ma, Peng‐Fei; Guo, Cen; Li, De‐Zhu
Abstract: Reticulate evolution is a common and important driving force in angiosperm evolution. In this study, we analyzed the phylogenetic signals of genomic regions with different inheritance patterns to understand the evolutionary process of organisms using species‐rich Himalaya–Hengduan taxa of bamboos ( Fargesia Franchet and Yushania Keng). We constructed phylogenetic trees using different sampling strategies and reconstruction methods based on genome skimming and double digest restriction‐site‐associated DNA sequencing data. We assessed the congruence of topologies generated from different datasets and employed several approaches to reveal the causes of phylogenetic incongruence, including the detection of hybridization and introgression using PhyloNetworks and the D ‐statistic test (ABBA‐BABA test). We found that, in the plastome‐based phylogeny, Fargesia bamboos can be clustered into three groups and Yushania was nested within one of them, which contradicts the nuclear–double digest restriction‐site‐associated DNA sequencing‐based phylogeny. Moreover, the genetic variation of chloroplast DNA is significantly correlated with geographical distribution. The strong signal of incomplete lineage sorting, hybridization, introgression, and cytoplasmic gene flow found among genera and species suggests that reticulate evolution is the main cause for the phylogenetic incongruence between nuclear and chloroplast datasets. Our results add evidence that genomes with different inheritance patterns can reveal distinct evolutionary histories of species and suggest that reticulate evolution is prevalent in rapidly diversifying groups.